2014
DOI: 10.1177/0363546514556741
|View full text |Cite
|
Sign up to set email alerts
|

Intratendinous Rotator Cuff Tears

Abstract: Transtendon suture bridge repair yielded satisfactory clinical and radiological outcomes in patients with intratendinous rotator cuff tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
0
19
1
Order By: Relevance
“…Rotator cuff tears occur as a result of normal ageing, excessive loading, and microtrauma. They are common in the general population and can have serious effects on a person’s work and life [3638]. Several therapies have been reported; however, the problem can be difficult to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Rotator cuff tears occur as a result of normal ageing, excessive loading, and microtrauma. They are common in the general population and can have serious effects on a person’s work and life [3638]. Several therapies have been reported; however, the problem can be difficult to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Good clinical outcomes have also been reported with TT repair in intratendinous PRCTs. 37 Park et al 37 reported clinical and radiographic outcomes in 33 patients (age 53.4 ± 9.1 years) with arthroscopically confirmed intratendinous PRCTs who underwent TT suture-bridge repair. At 4.6-year follow-up, 6.1% (N = 2) demonstrated Sugaya type III healing (ie, <50% normal tendon thickness without discontinuity).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Partial-thickness rotator cuff tears (PTRCTs) are detected in 13% to 40% of the adult population and in 70% of arthroscopically treated rotator cuff tears. 3,7,12 First-line treatment focuses on nonoperative therapy, including physical therapy, anti-inflammatory medication such as nonsteroidal anti-inflammatory drugs, and activity modification. 5,7,19,20 Even though nonoperative management is highly successful, approximately 29% to 40% of nonoperatively treated PTRCTs will increase to full-thickness rotator cuff tears.…”
mentioning
confidence: 99%